Effect of transplanting times on pollen and spikelet sterility, growth and yield of aman rice - Jalil, MA; Shelley, IJ; Pramanik, MHR; Karim, MA (Progressive Agriculture, 2017)
A field experiment was conducted to study the effect of planting dates on pollen/spikelet sterility, grain development and yield of hybrid rice in T. Aman season. The two varieties: Heera-4 (hybrid) and BINAdhan-7 (inbred) were transplanted on five consecutive dates at fifteen days interval viz. 15 July, 30 July, 15 August, 30 August and 15 September of 2011. The effect of variety and transplanting date showed significant variation in pollen sterility, grain growth & development, panicle length, filled grains panicle-1, spikelet sterility and grain yield. Pollen sterility was the highest in Heera-4 (>80%) consequently spikelet sterility for transplanting on 15 July while transplanting on 30 July low pollen sterility consequently spikelet sterility. Both early or late transplanting affected grain growth and development, enhanced pollen sterility as well as spikelet sterility and reduced grain yield. Late transplanting (30 August and 15 September) significantly reduced panicle length and filled grains panicle-1. Transplanting on 30 July gave low pollen sterility as well as spikelet sterility, high panicle length and high filled grains panicle-1 consequently greater grain yield in the varieties. Progressive Agriculture 27 (4): 400-408, 2016